IDENTIFICATION AND ANALYSIS OF A NOVEL HUMAN SURFACE CD5(−) B LYMPHOCYTE SUBSET PRODUCING NATURAL ANTIBODIES(,) - Kasaian, Marion T. (J Immunol, 1992)
The production of “natural” autoantibodies or antibodies, i.e., Ig that bind a variety of self- and/or exogenous Ag and arise independently of known immunization, is thought to be a feature of CD5(+) B lymphocytes. To determine whether other lymphocyte subsets exist that might be committed to the production of natural antibodies, human peripheral blood B cells were sorted on the basis of surface CD5 expression and differential expression of surface CD45RA (CD5(+)CD45RA(intermediate(int)), CD5(−) CD45RA(low(lo)), and CD5(−)CD45RA(high(hi))), and analyzed for the type of Ig produced after EBV infection and culture. Like their CD5(+) counterparts, most CD5(−)CD45RA(lo) B lymphocytes were precursors of cells producing IgM, a major proportion of which displayed the Ag-binding features of natural antibodies. In contrast, CD5(−)CD45RA(hi) B cells comprised a high frequency of IgG-producing cell precursors, possibly including memory B lymphocytes. Six of seven IgM mAb generated from sorted CD5(−)CD45RA(lo) B cells and three of four IgM mAb from sorted CD5(+) B cells were polyreactive, binding with different affinities (K(d), 10(−5) to 10(−8) M) to two or more Ag; the remaining mAb from CD5(−)CD45RA(lo) and the mAb from CD5(+) B cells each bound to a single Ag (K(d), 10(−7) to 10(−8) M), β-galactosidase and ssDNA, respectively. CD5(−)CD45RA(lo) B cells account for 4.1 ± 1.2% (mean ± SD in 11 healthy subjects; CD5(+) B cells, 23.3 ± 6.9%) of total B lymphocytes and display the features of quiescent cells. In a given individual, the number of CD5(−)CD45RA(lo) B cells remains constant over time. CD5(−)CD45RA(lo) and CD5(+) B cells bear surface CD11b and CD14, at densities and/or frequencies apparently higher than those of CD5(−)CD45RA(hi) B lymphocytes. Despite their surface CD5(−) phenotype, CD45RA(lo) B cells express CD5 mRNA at levels comparable with those of CD5(+) B lymphocytes, whereas CD5(−)CD45RA(hi) B cells express only trace amounts of CD5 mRNA. The commitment to natural antibody production and the degree of CD5 mRNA expression suggest that the newly defined CD5(−)CD45RA(lo) B cell subset is related to CD5(+) B lymphocytes, and may constitute the human homologue of the mouse Ly-1(−) “sister” B cell population.